Sub-Saharan Africa and Global Capital Markets - Sam Jones (Danish Institute for International Studies (DIIS), 2007)
Recent years have seen a considerable shift in economic conditions in sub-Saharan Africa. Economic growth has been robust, international reserves are on the rise and levels of external debt are falling. Combined with the global boom in commodity prices, as well as expansion of Chinese interests in the region, international investors are increasingly viewing Africa as a serious investment option. As a result of these trends, the landscape in which foreign donors have operated is changing rapidly. Constructive engagement with this agenda, taking account of the new opportunities and risks that access to global capital markets entails, is the message of a new study by Sam Jones, researcher in DIISs Trade and Development research unit. Access to capital markets: opportunities and risks Despite concerns that inflows of foreign capital market instruments may be detrimental to economic development, the study encourages a nuanced analysis of the pros and cons of different financing instruments. Access to foreign capital markets (equities, bonds and commercial bank lending) can be beneficial in the following ways:~-Lower the cost of financing throughout the economy -Support the development of domestic financial markets -Enhance discipline and transparency across markets -Provide longer-term finance for investment in the productive sectors Of course the risks of access to these flows need to be managed carefully. In particular, borrowing must be maintained at sustainable levels and speculative bubbles avoided. Where financial systems are weak, this is likely to require a cautious approach. Even so, over the medium-term, access to new sources of financing may provide a valid and sustainable exit strategy from dependence on foreign aid. As such dependence has characterized many countries in sub-Saharan Africa during the 1980s and 1990s, this emerging agenda demands to be taken seriously.
Keywords: 330